NEPHROPROTECTIVE ACTIVITY OF DECOCTION OF INDIGOFERA TINCTORIA (AVURI KUDINEER) AGAINST CISPLATIN-INDUCED NEPHROPATHY IN RATS: Pharmaceutical Science-Pharmacology - G. PRIYADARSINI; A. KUMAR; J. ANBU; ANJANA, ASHWINI; S. AYYASAMY (International Journal of Life Science and Pharma Research, 2012)
Cisplatin is widely used chemotherapeutic agent for the treatment of several human malignancies. The efficacy is dose dependent, but the significant risk of nephrotoxicity frequently inhibits the use of higher doses to maximize its anti-neoplastic effects. In the present investigation, the Avuri kudineer [Decoction of Indigofera tinctoria] made of indigo leaves AKL, the Avuri kudineer made of indigo root and leaves AKRL was evaluated for nephroprotective activity in Cisplatin induced renal damage in rats. Nephrotoxicity was induced in wistar albino rats by intra-peritoneal administration of Cisplatin 5mg/kg. Effect of concurrent administration of AKL and AKRL Avuri kudineer at a dose of 500 mg/kg and 1000mg/kg were given for respective animal groups by oral route was determined using serum creatinine and blood urea and change in body weight as indicators of kidney damage. The decoctions significantly decreased the cisplatin induced nephrotoxicity. Remarkable changes were observed in body weight, serum creatinine and urea levels. It was observed that the Avuri kudineer [AKRL] significantly protected the kidneys from injury than the Avuri kudineer [AKL]. Current study results showed that the Avuri kudineer [Decoction of Indigofera tinctoria] possess significant nephroprotective activity against cisplatin induced renal damage.